Diagnostic Performance of Chest CT-Scan and First RT-PCR Testing for COVID-19 in Iranian Population - Ramin Hamidi Farahani; Meysam Mosallaei; Ebrahim Hazrati; Naeim Ehtesham; Bahram Pakzad; Mehrdad Nasrollahzadeh Sabet; Emran Esmaeilzadeh (Tehran University of Medical Sciences, 2021)
No Abstract